Animals as Icebreakers: A Pilot Animal-Assisted Therapy Group for Veterans with Serious Mental Illness - Megan M., Pollock (International Journal of Psychosocial Rehabilitation, 2017)
The human-animal connection and healing effects of animals are evident throughout history from animals’ role in work, companionship, and medical interventions. Research scientifically supports two forms of human-animal connections: routine pet ownership and animal-assisted therapy. The purpose of this program development project was threefold: (to explore the current literature on animal-based interventions for psychiatric illness, (2) to describe a recently developed Animal Therapy in the Community group at the VA San Diego Healthcare System, and (3) to offer recommendations on future directions for including animals in therapeutic interventions forpersons diagnosed with serious mental illness. The Animal Therapy in the Community group occurred in the Psychosocial Rehabilitation and Recovery Center, which is an intensive outpatient program for veterans diagnosed with serious mental illness with psychosis. A total of eight veterans participated in this program. Given the small sample size, an emphasis was placed on qualitative, observational and anecdotal data. Based on the veterans’ reports to providers, there were improvements in three main areas: social interaction, keeping busy, and increased selfconfidence. These authors offer ten lessons to inform future providers interested in implementing an animal-assisted group as part of their treatment milieu.